Dive in the “Soul” of Corporate Social Responsibility Through the Philosophy of Tri Hita Karana - Fadilla Cahyaningtyas; Saluana Che Salleh (Fakultas Ekonomi dan Bisnis, Universitas Udayana bekerjasama dengan Ikatan Sarjana Ekonomi Cabang Bali, 2024)
This study employs a qualitative research methodology to examine Corporate Social Responsibility (CSR) practices within the